PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI LISAN SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS 6 - Rahman, Latip (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Communication skills are regarded as one of the key competencies that need to be developed in 21st-century learning. Mastery of communication skills constitutes an important competency that needs to be strengthened in the learning process in the 21st century. The reality of learning in elementary schools shows that not all students demonstrate active participation, particularly in expressing ideas, engaging in group discussions, and delivering presentations in front of the class. In this study, efforts to improve students’ oral communication skills in Pancasila Education learning were carried out through the implementation of the Problem Based Learning (PBL) model. The research was conducted with sixth-grade students at SD Negeri Cengal IV using the Classroom Action Research (CAR) method with a qualitative approach. The study was implemented through two iterative cycles following the Kemmis and Taggart model, which includes the stages of planning, action implementation, observation, and reflection. Research data were collected through observation techniques focusing on students’ involvement in discussion and presentation activities during the learning process. The research findings indicate a gradual improvement in students’ oral communication skills in each learning cycle. In the first cycle, students’ communication skills reached 79% in discussion activities and 75% in presentation activities. In the second cycle, these percentages increased to 91.6% in discussions and 87.5% in presentations. The development of students’ oral communication skills in Pancasila Education learning is supported by the implementation of the Problem Based Learning model, which is able to increase students’ participation in discussion and presentation activities. ABSTRAK Penguasaan keterampilan komunikasi merupakan bagian dari kompetensi penting yang perlu diperkuat dalam proses pembelajaran pada abad ke-21. Realitas pembelajaran di sekolah dasar menunjukkan bahwa tidak semua siswa menunjukkan keterlibatan aktif, khususnya dalam mengemukakan gagasan, mengikuti diskusi kelompok, serta melakukan presentasi di depan kelas. Peningkatan keterampilan komunikasi lisan siswa pada pembelajaran Pendidikan Pancasila dalam penelitian ini diupayakan melalui penerapan model pembelajaran Problem Based Learning (PBL). Pelaksanaan penelitian pada siswa kelas VI di SD Negeri Cengal IV dilakukan melalui metode Penelitian Tindakan Kelas (PTK) yang menggunakan pendekatan kualitatif. Pelaksanaan penelitian dilakukan melalui dua siklus yang berulang dengan mengikuti model Kemmis dan Taggart, yang mencakup tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data penelitian diperoleh melalui teknik observasi dengan fokus pengamatan pada keterlibatan siswa dalam kegiatan diskusi dan presentasi selama pembelajaran berlangsung. Temuan penelitian mengindikasikan adanya peningkatan bertahap pada keterampilan komunikasi lisan siswa di setiap siklus pembelajaran. Sebesar 79% keterampilan komunikasi siswa pada kegiatan diskusi dan 75% pada kegiatan presentasi diperoleh sebagai hasil penelitian pada siklus I. Pada siklus II, persentase tersebut mengalami peningkatan menjadi 91,6% pada diskusi dan 87,5% pada presentasi. Pengembangan keterampilan komunikasi lisan siswa dalam pembelajaran Pendidikan Pancasila didukung oleh penerapan model Problem Based Learning yang mampu meningkatkan partisipasi siswa dalam kegiatan diskusi dan presentasi.